PERAN CSR DALAM PELAKSANAAN MBS DI SDN 1 RANTODIOR ACEH TENGGARA - Khairi Sakinah; Lailatussaadah Lailatussaadah (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to analyze the role of Corporate Social Responsibility (CSR) in supporting the implementation of School-Based Management (SBM) at SDN 1 Rantodior, Southeast Aceh, with a qualitative approach. The data collection process was carried out through interviews with the principal, teachers, supervisors, and the community, direct observation to understand how CSR plays a role in improving educational facilities, training educators, and community involvement and analyzing documentation. The data were then analyzed using iminteractive and thematic models. The results of the study indicate that the role of CSR in the implementation of SBM at SDN 1 Rantodior Southeast Aceh. Found in two areas, namely the role of CSR in the Implementation of SBM Improving Educational Facilities Training for Teachers This CSR role contributes to the development of schools